CFO emphasis on value-based management: Performance implications and the challenge of CFO succession. (September 2019) - Firk, Sebastian; Schmidt, Torben; Wolff, Michael
Abstract: Top management support is often proclaimed as a crucial factor for the successful use of value-based management (VBM). Moreover, recent research indicates that CFOs play a leading role in shaping management accounting and, particularly, VBM. Although this suggests that CFO emphasis has a positive impact on the successful use of VBM, empirical research that considers the differentiating elements of VBM adopters is scarce. Therefore, this study empirically investigates the performance implications of CFOs placing emphasis on VBM and the challenge of upholding VBM emphasis following CFO succession. To accomplish this, we focus on a longitudinal sample of VBM adopters and assess CFO emphasis on VBM based on his/her remarks made during company conference calls. Our analyses provide empirical evidence that CFO emphasis enhances the performance of VBM adopters. This phenomenon can, however, become a significant issue for organizations when new CFOs take up office, as our results show that successor CFOs, who were not in charge of the initial implementation, typically place less emphasis on VBM. Nevertheless, we find that the VBM emphasis of successor CFOs can be perpetuated by tying their compensation to VBM. In line with this, additional tests indicate a negative impact of successor CFOs on the effectiveness of VBM only when compensation is not tied to VBM.